2019
DOI: 10.1080/21645515.2019.1692558
|View full text |Cite
|
Sign up to set email alerts
|

An educational intervention to improve attitudes regarding HPV vaccination and comfort with counseling among US medical students

Abstract: Many medical students are not comfortable recommending the human papillomavirus (HPV) vaccine because they do not feel prepared to discuss it with their patients. A prior study demonstrated that this is particularly a problem among unvaccinated students. Our purpose was to determine if medical student attitudes and comfort with counseling could be improved by attending a single lecture delivered by an expert on the topic. To assess the effects of the educational program, we conducted pre-and posttests on medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Considering the surveyed subset of health sciences students, and their future role in counselling on prevention themes, a comparison with the results of a recent published study by Berenson et al could be conducted. The authors assessed the effects of an educational program by means of a single lecture and delivered by an expert and found that this can improve medical students' attitudes and comfort with HPV vaccine counseling [39]. This evidence suggests that short educational interventions are already efficacious, but the presence of an expert open to discussion allows obtaining better results than reading informative material alone.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the surveyed subset of health sciences students, and their future role in counselling on prevention themes, a comparison with the results of a recent published study by Berenson et al could be conducted. The authors assessed the effects of an educational program by means of a single lecture and delivered by an expert and found that this can improve medical students' attitudes and comfort with HPV vaccine counseling [39]. This evidence suggests that short educational interventions are already efficacious, but the presence of an expert open to discussion allows obtaining better results than reading informative material alone.…”
Section: Discussionmentioning
confidence: 99%
“…Given the student lack of knowledge identified by our study, including material on HPV vaccination in the standard medical student curriculum could help increase physician recommendations for the HPV vaccine. 19 Our results showed that higher HPV-related cancer awareness and better knowledge on existence of vaccines again HPV may not be associated with an increase in vaccination uptake. The main limiting factor for vaccination again HPV in Ukraine is the high vaccine cost.…”
Section: Discussionmentioning
confidence: 61%
“…Another US‐based study on medical students showed that attending a single lecture given by an expert can improve medical students' attitudes and comfort with HPV vaccine counselling, especially if the students were not vaccinated themselves. Given the student lack of knowledge identified by our study, including material on HPV vaccination in the standard medical student curriculum could help increase physician recommendations for the HPV vaccine 19 …”
Section: Discussionmentioning
confidence: 99%
“…Berenson et al. found that only 31.3% (80/256) of medical students knew the CDC recommended schedule of follow up doses for those 15 years or older ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Topics covered included HPV virology, HPV-related cancers, epidemiology, vaccines, and comfort counseling. All studies reported improved knowledge following educational interventions ( 36 , 37 , 39 , 41 , 42 , 46 ).…”
Section: Resultsmentioning
confidence: 99%